The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Recent advances in natural gums as additives to help the construction and application of edible biopolymer gels: the example of hydrogels and oleogels - Wenbo Miao; Han Jiang; Xiaojing Li; Shangyuan Sang; Liming Jiang; Qianzhu Lin; Zhiheng Zhang; Long Chen; Jie Long; Aiquan Jiao; Jinpeng Wang; Zhengyu Jin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Navigating Asia’s sustainable growth trajectory: a cross-regional comparative analysis - Xinjie Li; Donghyun Choi; Jeong Hugh HAN; Po-Lin Lai; Yanfeng Liu (Environmental Science and Pollution Research, 2024)

Unveiling a novel mechanism: Reduction of graphene oxide by Lysinibacillus sp. through secretion of l-ascorbic acid - Yuanyuan Zhou; Ziyi Lin; Yonghe Han; Li Gan; Ying Cheng; Zuliang Chen (Chemosphere, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

Perfluorobutanoic acid weakens the heterogeneous aggregation of microplastics and microalgae: Perspective from physicochemical properties, extracellular polymeric substances secretion and DLVO theory - Yue Li; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Yu Huang; Haidong He; Zongshuo Han; Jiaqing Tao; Tao Lin (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Response of aerobic granular sludge to salinity fluctuations in formation, stability and microbial community structures - Jie Xu; Shichang Liu; Jiazhong Zhou; Lin Li; Xuejun Bi; Wenjie Han; Di Wu (Science of The Total Environment, 2024)

Risk hotspots and influencing factors identification of heavy metal(loid)s in agricultural soils using spatial bivariate analysis and random forest - Xiaohang Xu; Zhidong Xu; Longchao Liang; Jialiang Han; Gaoen Wu; Qinhui Lu; Lin Liu; Pan Li; Qiao Han; Le Wang; Sensen Zhang; Yanhai Hu; et al. (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Cnaphalocrocis medinalis granulovirus regulates apoptosis by targeting AIF1 and ASPP1 through tca-miR-3885-5p and tca-miR-3897-3p to promote infection - Nan Zhang; Guangjie Han; Chuanming Li; Lixin Huang; Qin Liu; Manman Lin; Bin Xu; Jian Xu (Pesticide Biochemistry and Physiology, 2024)

Long-term fallowing produces specific fungal taxa associated with soil carbon storage - Fang LI; Lin CHEN; Yue LI; Yanlai HAN; Yi WANG; Peipei LI; Shuiqing ZHANG; Jiabao ZHANG (Pedosphere, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Empowering sustainability: How digital agricultural extensions influence organic fertilizer choices among Chinese farmers - Lin Li; Jiliang Han; Yuchun Zhu (Journal of Environmental Management, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Modulating charge transfer and constructing synergistic bimetallic active sites for CO-SCR reactions in inverse spinel - Qin Li; Xiaorong Han; Lin Tao; Qiuju Qin; Xuechi Du; Yuzhu Liang; Bin Li; Zhengjun Chen; Liya Zhou; Lihui Dong (Journal of Environmental Chemical Engineering, 2024)

Integrating a high-energy activation method for the sustainable treatment of iron smelting slag, phosphogypsum, and arsenic-contaminated water - Donghui Chen; Jie Tan; Hong Li; Yanmin Lin; Fangming Nan; Qingwen Han; Wei Zhan (Journal of Environmental Chemical Engineering, 2024)

Unveiling the competitive mechanism between SO2 and PCDD/Fs on activated carbon adsorption - Jianwen Lai; Peiyue Wang; Yunfeng Ma; Zhongkang Han; Heidelore Fiedler; Xiaoqing Lin; Xiaodong Li (Journal of Environmental Chemical Engineering, 2024)

The hypoglycemic activity of buckwheat and the underlying mechanisms: A mechanistic review - Xiying Jin; Caian He; Ziwei Guo; Yixin Li; Yunlong Li; Jinming Gao; Min Wang; Lin Han (Food Bioscience, 2024)

Effects of relative humidity on atmospheric organosulfur species derived from photooxidation and nocturnal chemistry in a forest environment - Lijuan Li; Jianjun Li; Xin Zhang; Yue Lin; Rui Wang; Junji Cao; Yuemei Han (Environmental Pollution, 2024)

Molecular mechanism of immunotoxicity: Binding interaction between perfluorinated compounds and human immunoglobulin G - Qing Shi; Zekai Li; Wangzhiqian Zhao; Xiaojie Hu; Hefei Wang; Jian Wang; Miao Han; Lin Xu; Hao Sun; Chao Qin; Wanting Ling (Environmental Pollution, 2024)

Impacts of distinct residual aluminum on gypsum scaling in nanofiltration: Identification of key species - Jinjin Jia; Jinlong Wang; Dachao Lin; Jing Zhao; Hesong Wang; Longfeng Hu; Jiaxuan Yang; Han Zhang; Guibai Li; Heng Liang (Desalination, 2024)

Cation exchange strategy of ellagic acid-based microporous metal-organic framework for efficient CO2/N2 and CO2/CH4 separation - Chen-Ning Li; Zhi-Peng Tao; Lin Liu; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2024)

The source, transport, deposition and direct radiative effect of mineral dust over western China: A modeling study of July 2022 with focus on the Tibetan Plateau - Lin Liang; Zhiwei Han; Weiwei Chen; Jiawei Li; Mingjie Liang; Shujing Shen (Atmospheric Research, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Effects of salinity and temperature on growth performance, biochemical composition, and biosilification process of Cyclotella cryptica - Yicun Zhao; Yan Sun; Zhengfeng Zhu; Yuhang Li; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Algal Research, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Experimental investigation of slamming pressure on 3D bow flare - Yihang Shan; Hui Li; Bingbing Han; Zhiyong Sun; Lin Lu; Ruixiang Liu; Yi Liu; Hao Guo (Ocean Engineering, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

The bifunctional impact of polylactic acid microplastics on composting processes and soil-plant systems: Dynamics of microbial communities and ecological niche competition - Yufan Wang; Yiqiong Zhang; Zhouchang Zhang; Qing Liu; Tengqi Xu; Jiaxi Liu; Siqi Han; Tianjiao Song; Li Li; Xiaomin Wei; Yanbing Lin (Journal of Hazardous Materials, 2024)

Influence of perfluorooctanoic acid on alkaline anaerobic fermentation of waste activated sludge: Perspective from volatile fatty acids production and sludge reduction - Zhilin Zhao; Xiaoying Zheng; Shanshan Yang; Haidong He; Zongshuo Han; Wenfei Li; Tao Lin; Hang Xu (Journal of Environmental Management, 2024)

Lipid fingerprinting and geographical origin identification of large yellow croaker (Larimichthys crocea) using UHPLC-QTOF-MS - Haolei Han; Xiangxin Lin; Yuxuan Wu; Houru Li; Qi Jia; Changmin Hu; Yixuan Lin; Guangqin Liao; Yongzhong Qian; Jing Qiu (Food Research International, 2024)

Corrigendum to ‘Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon’ [Environ. Pollut., Volume 361, 15 November 2024, 124750 - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Heidelore Fiedler; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Fiedler Heidelore; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Reducing defects in hard carbon graphite domain: Employing a fully dynamic bonding with a multi-crosslinked biomass-based binder for enhanced sodium ion storage - Jiaqi Jiao; Han Lu; Conghua Yi; Dongjie Yang; Xuezhi Zeng; Jinxin Lin; Hongqiang Li (Chemical Engineering Journal, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Comparative study on environmental and economic assessment of straw heating across administrative areas scale of rural China - Tong Li; Guoxia Wei; Hanqiao Liu; Hailong Zhao; Yuwen Zhu; Yanfei Lin; Qianlong Han; Yifan Chen; Yanzhang Wang (The International Journal of Life Cycle Assessment, 2024)

Warming mitigates the effects of nitrogen addition on the soil diazotrophic community in a subtropical forest - Jiling Cao; Lin Li; Yu Han; Zhiyuan Liu; Faying Lai; Yusheng Yang (Applied Soil Ecology, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Intelligent Layout Method of Ship Pipelines Based on an Improved Grey Wolf Optimization Algorithm - Yongjin Lu; Kai Li; Rui Lin; Yunlong Wang; Hairong Han (Journal of Marine Science and Engineering, 2024)
Ship piping arrangement is a nondeterministic polynomial problem. Based on the advantages of the grey wolf optimization (GWO) algorithm, which is simple, easy to implement, and has few adjustment parameters and fast convergence speed, the study adopts the grey wolf optimization (GWO) algorithm to solve the ship piping arrangement problem. First, a spatial model of ship piping arrangement is established. The grid cell model and the simplified piping arrangement environment model are established using the raster method. Considering the piping arrangement constraint rules, the mathematical optimization model of piping arrangement is constructed. Secondly, the grey wolf optimization algorithm was optimized and designed. A nonlinear convergence factor adjustment strategy is adopted for its convergence factor. Powell’s algorithm is introduced to improve its local search capability, which solves the problem that the grey wolf algorithm easily falls into the local optimum during the solving process. Simulation experiments show that compared with the standard grey wolf algorithm, the improved algorithm can improve the path layout effect by 38.03% and the convergence speed by 36.78%. The improved algorithm has better global search ability, higher solution stability, and faster convergence speed than the standard grey wolf optimization algorithm. At the same time, the algorithm is applied to the actual ship design, and the results meet the design expectations. The improved algorithm can be used for other path-planning problems.

Mineralogy and geochemistry of the Cambrain Shuijingtuo Formation black shales from Western Hubei, China: implications on enrichment of critical metals and paleoenvironment - Yuan Wang; Jing Li; Yang Lin; Xinguo Zhuang; Vanlong Hoang; Peng Wu; Xin Luo; Han Zhang; Xiaoyang Zhang (Frontiers in Marine Science, 2024)
Black shales have attracted the attention of numerous researchers not only due to their high potential as hydrocarbon source rocks and shale gas reservoirs, but also to the enrichment of critical metal elements in black shale series. Black shale of the Cambrian Shuijingtuo Formation is one of the most important black shales in the Yangtze platform. This paper conducts integrated research on the mineralogical and geochemical characteristics of this black shale from the Luojiacun section in Western Hubei Region, aiming at elaborating the enrichment mechanism of elevated critical metal elements in the Shuijingtuo black shale. Minerals in the Shuijingtuo black shale are predominantly composed of quartz (avg. 43.0%) and clay minerals (avg. 32.5%), with small proportions of calcite, albite, clinochlore, and pyrite. The Shuijingtuo black shale is characterized by high total organic carbon (TOC, avg. 3.9%) content and enriched in V-Ni-Cr-U and Sr-Ba critical metal assemblages. The elevated V, Cr, Ni, and U present dominant organic affinities, while Sr and Ba are closely correlated to calcite and pyrite, respectively. The enrichment of V-Cr-Ni-U critical element assemblages in Shuijingtuo black shale are ascribed to the high primary productivity, anoxic depositional conditions, marine biologic production, and low-temperature hydrothermal activities. The enrichment of Sr and Ba is related to the high primary productivity and anoxic depositional conditions, respectively.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Effects of photochemical aging on the molecular composition of organic aerosols derived from agricultural biomass burning in whole combustion process - Lijuan Li; Yuemei Han; Jianjun Li; Yue Lin; Xin Zhang; Qiyuan Wang; Junji Cao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction of Cu2-xS@Zn0.5Cd0.5S S-scheme heterojunction with core-shell structure for efficient photocatalytic hydrogen production and tetracycline degradation - Zhiqiang Ai; Xiaoya Zhu; Liwei Lin; Han Li; Yanan Wang; Qian Liang; Man Zhou; Song Xu; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

Supplementation with a phenolic-rich fraction from Ilex kudingcha improves inflammatory stress, gastrocnemius weights, and foreleg muscle grip strength in murine squamous cell carcinoma (SCC7)-bearing mice - Han-Chen Chao; Wan-Li Yang; Li-Wha Wu; Jin-Yuarn Lin (Food Bioscience, 2024)

Upcycling of Pb from lead smelting residues to lead halide perovskite for piezocatalytic hydrogen production - Xiaofeng Mo; Mengye Wang; Han Song; Jie Li; Zhen Wu; Zhang Lin (Chemical Engineering Journal, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Unlocking the photothermal conversion capacity of lignin and lignin-derived materials - Yanhua Guan; Hai Liu; Ying Han; Yuanjiamei Zhou; Li Yan; Lin Dai; Chuanling Si (Chemical Engineering Journal, 2024)

Mechanically customizable lignin bio-elastomers based on tailorable multiscale microstructures - Dengfeng Wang; Mengyuan Diao; Yaotao Shan; Han Wu; Lin Liu; Zihan Li; Haojie Hong; Juming Yao (Chemical Engineering Journal, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

An Anisotropic Thermal–Mechanical Coupling Failure Criterion for Slate - Meng-Chia Weng; Shih-Shiang Lin; Chih-Shan Lee; Wei-Han Wu; Jia Han Li; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2024)
This study investigates the thermal–mechanical behavior of slates in geothermal reservoirs and establishes an anisotropic thermal–mechanical coupling failure criterion. Slate samples obtained from a geothermal site were subjected to a series of direct-shear and triaxial-compression tests at various confining pressures and temperatures. The results showed that the orientation angle within a specific range caused shear sliding failure of the slate, primarily due to foliation strength; beyond this range, intrinsic rock properties led to different failure modes. Elevated temperatures significantly diminished the strength anisotropy of the slate. These findings provided a foundation for the development of an anisotropic thermal–mechanical coupling failure criterion. The validity of the proposed criterion, which incorporates both the orientation angle and thermal degradation effects, was demonstrated through experimental results. A three-dimensional surface diagram was constructed to visualize the relationship between the temperature, orientation angle, and failure principal stress, highlighting the anisotropic thermal-degradation characteristics of the slate under varying confining pressures. This study enhances the understanding of the thermal–mechanical behavior of these materials in geothermal reservoirs.

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Construction of Covalent organic frameworks with bex topology for efficient photocatalytic hydrogen production - Lin Wang; Changzhi Han; Jingwen Pan; Shuo Li; Jia-Xing Jiang; Fengyun Guo; Shiyong Gao; Dongbo Wang; Yong Zhang (Chemical Engineering Journal, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Global quantitative synthesis on the patterns and drivers of funneling ratio and enrichment ratio for stemflow - Meng-Di Wu; Zhi-Yun Jiang; Xiao Yang; Buerlan Yeerbolati; Lin Huang; Ying-Yin Zhong; Han-Wen Zhang; Xiao-Yan Li (CATENA, 2024)

Feasibility of simultaneous optimization of Anammox start-up and nitrogen removal performance by intermittent dosing of nanoscale zero-valent iron - Zongshuo Han; Ruijie Hu; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Haidong He; Tao Lin; Hang Xu (Bioresource Technology, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

An axenic strain reveals the responses of Phaeodactylum tricornutum to external organic carbon - Zhengfeng Zhu; Zhichao He; Jian Li; Chengxu Zhou; Yanrong Li; Lin Zhang; Xiaohui Li; Spiros N. Agathos; Jichang Han (Journal of Oceanology and Limnology, 2024)

Anisotropy measurements and characterization of the Qingshankou shale - Qing-feng Li; Xue-hong Yan; Wei-lin Yan; Li Ren; Peng Wang; Jian-qiang Han; Xue Xia; Hao Chen (Applied Geophysics, 2024)

Blood–Brain Barrier Permeability is Affected by Changes in Tight Junction Protein Expression at High-Altitude Hypoxic Conditions—this may have Implications for Brain Drug Transport - Guiqin Liu; Qian Wang; Lu Tian; Mengyue Wang; Delong Duo; Yabin Duan; Yue Lin; Junjun Han; Qiangqiang Jia; Junbo Zhu; Xiangyang Li (The AAPS Journal, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Size-dependent deleterious effects of nano- and microplastics on sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Xiaofang Han; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Chunqiu Zhang; Xuejun Shang; et al. (Toxicology, 2024)

Long-term mulched drip irrigation enhances the stability of soil aggregates by increasing organic carbon stock and reducing salinity - Mingdong Tan; Wenhao Li; Rui Zong; Xuanzhi Li; Yue Han; Pengcheng Luo; Yam Prasad Dhital; Haixia Lin; Haiqiang Li; Zhenhua Wang (Soil and Tillage Research, 2024)

Core microbial taxonomies that maintain high organic carbon content in upland soil - Fang Li; Lin Chen; Zhongjun Jia; Jiabao Zhang; Zhanhui Zhao; Yanlai Han; Yi Wang (Science of The Total Environment, 2024)

Deep learning-based dispersion prediction model for hazardous chemical leaks using transfer learning - Xiaoyi Han; Jiaxing Zhu; Haosen Li; Wei Xu; Junjie Feng; Lin Hao; Hongyuan Wei (Process Safety and Environmental Protection, 2024)

Sedimentation history linked to global change in the alpine Damqu Wetland of the Yangtze River headwater in interior Tibetan Plateau - Qinjing Shen; Xinqi Feng; Yinjun Zhou; Penghui Lin; Yuexin Liu; Yuansen Lai; Junfeng Han; YuJiao Liu; Yixuan Wang; Shuai Zhu; Zhijing Li; Zhongping Lai (Quaternary Geochronology, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Straw returning and nitrogen reduction: Strategies for sustainable maize production in the dryland - Miaomiao Zhang; Ning Yang; Shiguang Wang; Xiaoqing Han; Pengfei Dang; Guoqing Li; Shuyue Wen; Lin Zhang; Jiquan Xue; Xiaoliang Qin; Kadambot H.M. Siddique (Journal of Environmental Management, 2024)

Anion substitution-induced CuCoSe hollow nanotubes as multifunctional electrode materials for supercapacitors and overall water splitting - Zifeng Zeng; Zhifeng Gao; Zicheng Guo; Xiaowei Xu; Ying Li; Lin Lin; Runping Jia; Sheng Han (Fuel, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Enhanced rheological and 3D-printing properties of high internal phase emulsions stabilized by egg white microgels synergized with konjac gum/xanthan gum - Xiliang Yu; Lin Han; Qinggang Xu; Shengjie Li; Sangeeta Prakash; Xiuping Dong (Food Hydrocolloids, 2024)

Novel tri-solvent amines absorption for flue gas CO2 capture: Efficient absorption and regeneration with low energy consumption - Guanghuan Li; Xuehua Shen; Xianfeng Jiao; Feng Xie; Jiali Hua; Han Lin; Feng Yan; Hao Wu; Zuotai Zhang (Chemical Engineering Journal, 2024)

Effects of Salt Content and Freeze-Thaw Conditions on Dynamic characteristics and its microscopic mechanism of Chloride Silty Clay - Yaqin Zhang; Ping Yang; Lin Li; Ting Zhang; Linliang Han (Cold Regions Science and Technology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Dynamic Response Analysis of a Subsea Rigid M-Shaped Jumper under Combined Internal and External Flows - Guangzhao Li; Wenhua Li; Shanying Lin; Fenghui Han; Xingkun Zhou (Journal of Marine Science and Engineering, 2024)
To analyze the dynamic response of a rigid M-shaped jumper subjected to combined internal and external flows, a one-way coupled fluid–structure interaction process is applied. First, CFD simulations are conducted separately for the internal and external fluid domains. The pressure histories on the inner and outer walls are exported and loaded into the finite element model using inverse distance interpolation. Then, FEA is performed to determine the dynamic response, followed by a fatigue assessment based on the obtained stress data. The displacement, acceleration, and stress distribution along the M-shaped jumper are obtained. External flow velocity dominates the displacements, while internal flow velocity dominates the vibrations and stresses. The structural response to the combined effect of internal and external flows, plus the response to gravity alone, equals the sum of the structural responses to internal flow alone and external flow alone. Fatigue damage is calculated for the bend exhibiting the most intense vibration and higher stress levels, and the locations with significant damage correspond to areas with high maximum von Mises stress. This paper aims to evaluate multiple flow fields acting simultaneously on subsea pipelines and to identify the main factors that provide valuable information for their design, monitoring, and maintenance.

Comparative Assessment of the Environmental and Economic Performance of Two Straw Utilization Pathways in China - Tong Li; Guoxia Wei; Hanqiao Liu; Yuwen Zhu; Yanfei Lin; Qianlong Han (BioEnergy Research, 2024)

Kinetic isotope effect of decomposing fatty acids in the continental shelf sediment of the northern South China Sea - Tengteng Wang; Chuhan Lin; Han Zhang; Jiying Li; Lifang Wang; Yaohua Luo; Jie Liu; Jiaheng Shen; Tiantian Tang (Frontiers in Marine Science, 2024)
As a response of the coastal oceans to more severe anthropogenic disturbance, increasing coastal primary production has been more frequently observed in recent years. This raises the question of how this progressive change reshapes the long-term carbon sequestration in the coastal oceans. With this question in mind, we investigated the sediment organic matter (OM) preserved on the shelf of the northern South China Sea (NSCS) where high primary production has been observed. Across this sediment core, relatively low total organic carbon content of around 0.60% was observed. Fatty acids with less carbon numbers exhibit exponential decreases downward with degradation rate constants ranging from 0.10 to 0.17 y -1 , no matter they were from single sources (14:0 presumably from marine OM and ai -15:0, i -15:0, 15:0 from bacterial OM) or mixed sources (16:0). Meanwhile fatty acids with more carbon numbers, either 18:0 and 24:0 from mixed sources, or 26:0 and 28:0 presumably from terrestrial input, were less varied in concentrations with depth. This demonstrates a preferential decomposition of labile fatty acids during the early diagenesis of coastal sediment organic matter. A decrease of labile fatty acids δ 13 C values was observed with the decomposition, from which kinetic isotope fractionations were predicted ranging from 0.7 to 1.5‰. This provides an isotopic constraint of the mixing model to quantify labile organic matter from terrestrial input and local phytoplankton production, from which declined contribution of local phytoplankton production to labile fatty acids was identified in more recent sediment. This finding together with the low organic carbon content and rapid removal of fatty acids in the top sediment, demonstrates the poor preservation of labile organic matter on the shelf of NSCS, implying that the increasing primary production has not enhanced the coastal carbon sequestration yet, but rather leads to more intensified respiration with a potential risk to increase the CO 2 outgassing from the coastal oceans.

Correction: Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2024)

Global diversity of airborne pathogenic bacteria and fungi from wastewater treatment plants - Ying Wang; Wenwen Wang; Xuezheng Yu; Zixuan Wang; Ziyu Zhou; Yunping Han; Lin Li (Water Research, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Soil microorganisms play an important role in the detrimental impact of biodegradable microplastics on plants - Jiaxi Liu; Siqi Han; Peiyuan Wang; Xiaofeng Zhang; Jiuyu Zhang; Lijun Hou; Yiqiong Zhang; Yufan Wang; Li Li; Yanbing Lin (Science of The Total Environment, 2024)

Novel Janus polyurethane sponges with asymmetric wettability enabling all-weather stable and efficient remediation of crude oil spills in harsh environments - Wenqing Han; Yehai Yan; Huifang Wang; Peng Li; Haoting Lin; Jinzhong Li; Jian Cui; Guangfa Zhang (Journal of Water Process Engineering, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Green mechanochemical activation of solid persulfate to remove PAHs in soil: Performance and mechanism - Junke Zhang; Kexiao Han; Wentao Jiao; Peidong Su; Daxuan Wang; Jun Zhu; Mingshan Zhu; Lin Li (Journal of Hazardous Materials, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

BaO-modified finger-like nickel-based anode for enhanced performance and durability of direct carbon solid oxide fuel cells - Lin Li; Yujiao Xie; Tingting Han; Jinjin Zhang; Fangyong Yu; Gen Li; Jaka Sunarso; Naitao Yang; Yongdan Li (Fuel, 2024)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Growth increase and gonadal dysfunction of the lined seahorse triggered by zinc exposure - Xue Han; Chunyan Li; Geng Qin; Xin Wang; Bo Zhang; Qiang Lin (Aquatic Toxicology, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

Environment-economic comparison of potential alternative fuel heavy-duty trucks in China - Xizhao Zhang; Zhenhong Lin; Han Hao; Xu Hao; Zhichao Wang; Shunxi Li (Transportation Research Part D: Transport and Environment, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Salinity influence on adsorption of lipid molecules in clay minerals: Results from experiments and calculations - Xiao Gao; Zuozhen Han; Gang Zhou; Lin Li; Xiaowei Lyu; Yanyang Zhao; Wenjie Chen; Zhenhua Qi; Fang Liu; Qingqiang Meng; Michael Steiner; Chao Han (Journal of Environmental Chemical Engineering, 2024)

In-depth impact evaluation of binders on the mechanical properties and CO2 capture performance of CaO-based particles - Xuehua Shen; Ruiheng Zhang; Yiping Su; Han Lin; Feng Xie; Yingying Cai; Guanghuan Li; Jiali Hua; Feng Yan; Zewei Quan; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2024)

Polysaccharides from Auricularia cornea var. Li.: Structural alterations during in vitro digestion and its potent immunomodulatory properties on macrophages - Nan Lin; Minmeng Li; Zixuan Han; Xiaojuan Liu; Jialin Qu; Xinhui Wang; Xuchang Duan; Caian He (Food Bioscience, 2024)

Encapsulation and protection of β-carotene in Pickering emulsions stabilized by chitosan-phytic acid-cyclodextrin nanoparticles - Qianzhu Lin; Han Jiang; Xiaojing Li; David Julian McClements; Shangyuan Sang; Jinpeng Wang; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Food Bioscience, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Engineering of local electron properties optimization in single-atom catalysts enabling sustainable photocatalytic conversion of N2 into NH3 - Tianren Liu; Wensheng Zhang; Qingmei Tan; Weilong Lian; Haiting Lin; Jianshen Li; Dongxue Han; Yingying Fan; Dongdong Qin; Li Niu (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Impacts of open biomass burning in Southeast Asia on atmospheric PM2.5 concentrations over south China from 2009 to 2018 - Jie Li; Wenxuan Fan; Jian Wu; Zhiwei Han; Jiawei Li; Chuwei Zhang; Lin Liang (Atmospheric Environment, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Environmental and economic analysis of the transformation of paper mill sludge treatment technologies in China - Yanfei Lin; Guoxia Wei; Hanqiao Liu; Kai Li; Yuwen Zhu; Qianlong Han; Yunzhen Yang; Yi Lian (Environmental Science and Pollution Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Identification of SNPs and candidate genes associate with growth performance in all-female mandarin fish (Siniperca chuatsi) by a genome-wide association study - Dingrui Liu; Jin Zhang; Zhenjiang Zou; Chen Long; Jiaqi Lin; Junyan Zeng; Jingpeng Hou; Linqiang Han; Yanlin Jiang; Shuisheng Li; Yong Zhang (Aquaculture, 2024)

Potential pathogenic microorganisms in rural wastewater treatment process: Succession characteristics, concentration variation, source exploration, and risk assessment - Jun Zhan; Su Xu; Yingming Zhu; Yunping Han; Lin Li; Junxin Liu; Xuesong Guo (Water Research, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Ilex kudingcha’s phenolic-rich fraction inhibits murine squamous cell carcinoma (SCC7) through restoring adaptive immunity and Th1-polarized immune balance in vitro and in vivo - Han-Chen Chao; Li-Wha Wu; Jin-Yuarn Lin (South African Journal of Botany, 2024)

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Variability in molecular composition and optical absorption of atmospheric brown carbon aerosols in two contrasting urban areas of China - Yue Lin; Yuemei Han; Guohui Li; Lijuan Li; Xin Zhang; Junji Cao (Science of The Total Environment, 2024)

Occurrence and spatiotemporal distribution of natural and synthetic steroid hormones in soil, water, and sediment systems in suburban agricultural area of Guangzhou City, China - Hang Lin; Liangzhuo Zhou; Shudong Lu; Han Yang; Yongtao Li; Xingjian Yang (Journal of Hazardous Materials, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Dinotefuran exposure alters biochemical, metabolomic, gut microbiome, and growth responses in decapoda pacific white shrimp Penaeus vannamei - Zhenqiang Fu; Zhiyu Lin; Kaiqi Huang; Zhenfei Li; Zhi Luo; Fenglu Han; Erchao Li (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Study on the mechanism of natural polysaccharides on the deastringent effect of Triphala extract - Jun Liu; Pinhu Wang; Haozhou Huang; Xingliang Xie; Junzhi Lin; Youde Zheng; Li Han; Xue Han; Dingkun Zhang (Food Chemistry, 2024)

Fabrication of starch-based oleogels using capillary bridges: Potential for application as edible inks in 3D food printing - Wenbo Miao; Yijie Fu; Zhiheng Zhang; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Han Jiang; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Self-supporting honeycomb coaxial carbon fibers: A new strategy to achieve an efficient hydrogen evolution reaction both in base and acid media - Jiaqi Lin; Duanduan Yin; Wurigamula He; Lili Wang; Bin Yue; Tianqi Wang; Dan Li; Ce Han; Xiangting Dong (Chemical Engineering Journal, 2024)

Genome-wide characterization of SmZHD gene family and the role of SmZHD12 in regulating anthocyanin biosynthesis in eggplant (Solanum melongena L.) - Qian Chen; XinQin Liu; Han Zhang; JinDi Wang; Lin Du; ZiWei Zhao; ShaoHang Li; YongJun He (Plant Cell Reports, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Recent advances in the formation and identification of nanoparticle protein coronas and their effects on the digestion and absorption of polyphenols - Zhiheng Zhang; Han Jiang; Wenbo Miao; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Trends in Food Science & Technology, 2024)

Development of magnetic fluorescence aptasensor for sensitive detection of saxitoxin based on Fe3O4@Au-Pt nanozymes - Lin Zhu; Wei Zeng; Yueqing Li; Yu Han; Jing Wei; Long Wu (Science of The Total Environment, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Flow pattern evolution and flow-induced vibration response in multiphase flow within an M-shaped subsea jumper - Wenrui Song; Wenhua Li; Shanying Lin; Xingkun Zhou; Fenghui Han (Ocean Engineering, 2024)

New fossils reveal the Paleogene establishment of relict Craigia (Malvaceae) in its extant range - Jia Li; Shi-Tao Zhang; Xue-Yan Li; Cong-Li Xu; Yuan Zhu; Ruo-Han Zuo; Lin-Bo Jia (Palaeoworld, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Recycling of waste polyethylene in asphalt and its performance enhancement methods: A critical literature review - Hui Li; Yuzhao Han; E Guangxun; Yang Sun; Lei Wang; Xufei Liu; Jiaxing Ren; Zhijie Lin (Journal of Cleaner Production, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Study on lean combustion of ammonia-hydrogen mixtures in a pre-chamber engine - Jinlu Huo; Tongbin Zhao; He Lin; Jinhua Li; Wei Zhang; Zhen Huang; Dong Han (Fuel, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Multifunctional enhanced energy density of flexible wide-temperature supercapacitors based on MXene/PANI conductive hydrogel - Lin Han; Yueqin Li; Chen Chen; Lingke Liu; Zichun Lu (Chemical Engineering Journal, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

Sea Cucumber Viscera Contains Novel Non-Holostane-Type Glycoside Toxins that Possess a Putative Chemical Defense Function - Yanfang Liu; Zhen Lu; Zhi Yan; Ainuo Lin; Shaoshuai Han; Yaxi Li; Xiao Yang; Xiaodong Li; Xiuli Yin; Ranran Zhang; Ke Li (Journal of Chemical Ecology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

The response and factors of microbial aerosol emission from the sludge bio-drying process - Ying Wang; Lin Li; Jiawei Ma; Yunping Han (Waste Management, 2024)

Neurotoxic effects induced by flunitrazepam and its metabolites in zebrafish: Oxidative stress, apoptosis, and histone hypoacetylation - Yingjun Qin; Yajing Huang; Wenting Lin; Rui Huang; Kan Li; Xing Han; Yuan Ren (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

Polystyrene microplastics enhanced the effect of PFOA on Chlorella sorokiniana: Perspective from the cellular and molecular levels - Zhilin Zhao; Xiaoying Zheng; Zongshuo Han; Yue Li; Haidong He; Tao Lin; Hang Xu (Journal of Hazardous Materials, 2024)

UV-induced photodegradation of emerging para-phenylenediamine quinones in aqueous environment: Kinetics, products identification and toxicity assessments - Wei Wang; Guodong Cao; Jing Zhang; Han Qiao; Huankai Li; Biwei Yang; Yanyan Chen; Lin Zhu; Yuecheng Sang; Lei Du; Zongwei Cai (Journal of Hazardous Materials, 2024)

Mitigating heavy metal volatilization during thermal treatment of MSWI fly ash by using iron(III) sulfate as a chlorine depleting agent - Siyu Han; Kailun Chen; Fanzhi Meng; Yuchen Gao; Jinglin Li; Li Lin; Weikai Qin; Jianguo Jiang (Journal of Hazardous Materials, 2024)

Aboveground plants determine the exchange of pathogens within air-phyllosphere-soil continuum in urban greenspaces - Changyi Lu; Zufei Xiao; Hu Li; Ruixia Han; Anqi Sun; Qian Xiang; Zhe Zhu; Gang Li; Xiaoru Yang; Yong-Guan Zhu; Qing-Lin Chen (Journal of Hazardous Materials, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

A study on the demographic differences in visual impact assessments of the external space of electric vehicle battery swapping stations - Lin Zhang; Chenping Han; Tao Gu; Guanjun Li; Xiwu Qi; Jingjing Zhao (Environmental Impact Assessment Review, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

Prediction of thermal conductivities of insulation materials under water immersion and freeze–thaw conditions for tunnels in cold regions - Fenglei Han; Zonghan Liu; Jiazheng Li; Wenbing Yu; Qixiang Yan; Yuanfu Zhou; Shuzhen Zhang; Lin Chen (Tunnelling and Underground Space Technology, 2024)

Identification of surface water - groundwater nitrate governing factors in Jianghuai hilly area based on coupled SWAT-MODFLOW-RT3D modeling approach - Lu Zhang; Xue Li; Jiangbo Han; Jin Lin; Yunfeng Dai; Peng Liu (Science of The Total Environment, 2024)

Impacts of seasonal variation on volatile fatty acids production of food waste anaerobic fermentation - Weikai Qin; Siyu Han; Fanzhi Meng; Kailun Chen; Yuchen Gao; Jinglin Li; Li Lin; Endian Hu; Jianguo Jiang (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

A modified methodology to substitute U-shape well using a single well with fracture network: Design and performance - Lin Jia; Kewen Li; Yun Han; Chi Zhang; Lipeng Zhao (Geothermics, 2024)

ZrO2-MoO3/modified lotus stem biochar catalysts for catalytic aquathermolysis of heavy oil at low-temperature - Yiya Wang; Riyi Lin; Liqiang Zhang; Xinlu Han; Jinyu Li; Chenxing Huang; Qiwei Dong; Pengyu Chen; Huanan Li; Xinwei Wang (Fuel, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Diisobutylamine mediated CO2 mineralization and CaCO3 production from municipal solid waste incineration fly ash as raw ingredient and regeneration reagent - Kailun Chen; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yuchen Gao; Weikai Qin; Endian Hu; Jianguo Jiang (Chemical Engineering Journal, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

The changes and correlation of IL-6 and oxidative stress levels in RAW264.7 macrophage cells induced by PAHs in PM2.5 - Jiaxin Liu; Hongqiu Li; Ziwei Guo; Xiang Xiao; Angelo Viscardi; Rongqi Xiang; Haobiao Liu; Xue Lin; Jing Han (Environmental Geochemistry and Health, 2024)

Long-term fertilization affects microbial necromass accumulation by regulating nutrient and enzymatic stoichiometry in a calcareous Fluvisol - Changdong Han; Lin Chen; Xiuli Xin; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Yue Li; Ling Ma; Jiabao Zhang (Applied Soil Ecology, 2024)

Investigating the diurnal effects of on-street population and streetscape physical environment on street theft crime: A machine learning and negative binomial regression approach using street view images - Han Yue; Lin Liu; Chong Xu; Guangwen Song; Jianguo Chen; Li He; Lian Duan (Applied Geography, 2024)

Corrigendum to “Leaf hydraulic distance is a good predictor of growth within and across conifer species in a Taiga ecosystem” [AgriculturalandForestMeteorology342(2023)109710] - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Warming effects on C:N:P stoichiometry and nutrient limitation in terrestrial ecosystems - Hongwei Xu; Minggang Wang; Chengming You; Bo Tan; Lin Xu; Han Li; Li Zhang; Lixia Wang; Sining Liu; Guirong Hou; Yang Liu; Zhenfeng Xu; et al. (Soil and Tillage Research, 2024)

Acid controlled washing of municipal solid waste incineration fly ash: Extraction of calcium inhibiting heavy metals and reaction kinetics - Kailun Chen; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yuchen Gao; Weikai Qin; Jianguo Jiang (Science of The Total Environment, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

Effects of comb-like poly-α-olefins on the cold flow properties of diesel fuel - Honggang Wang; Xiaokang Zhang; Xiuwei Lei; Li Chen; Songyue Wang; Hualin Lin; Sheng Han (Fuel, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

Efficient removal of endocrine disruptors using nano zero-valent iron loaded organo-attapulgite: Mechanism and factors - Lei Dong; Li Lin; Guochuan Yin; Yueqi Cao; Xiong Pan; Han Zheng; Hongwu Jiang; Weijie Wu (Chemical Engineering Journal, 2024)

Obtainment and Inoculation of Acinetobacter pittii Strain JJ-2, and Combined Action with Plants for Formaldehyde and CO2 Removal: A Research Study - Jiaochan Zhong; Silan Chen; Shujie Lin; Yinjuan Jia; Han Li; Ting Zhan; Jian Li (Current Microbiology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Phenotypic characteristics and immune response of Procypris merus following challenge with aquatic isolate of Klebsiella pneumoniae - Wenyu Liao; Dongdong Wei; Mingzhu Liu; Lin Huang; Bingzheng Li; Yunyi Wei; Shuyu Han; Shuaishuai Huang; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2024)
Currently, aquaculture is a relatively mature industry; however, disease problems are continuously threatening the industry and hindering its development to a certain extent. Klebsiella pneumoniae is one of the zoonotic bacteria widely present in different hosts and has caused some degree of harm to the aquaculture industry, posing a potential threat to the water environment and indirectly also affecting human food safety issues. In this study, K. pneumoniae was isolated from the aquaculture environment, named as ELD, and subjected to pathogenic and immunological related studies. The results of the study showed that the strain carries at least four virulence‐related genes, magA , wabG , ureA and uge , and has developed resistance to at least seven antibacterial drugs, such as amoxicillin, doxycycline, rifampicin, and so on. Moreover, the strain is highly pathogenic and is capable of causing systemic clinical foci in Procypris merus . In addition, after infection with K. pneumoniae , the expression of IL‐1β, IL‐8, HSP70 and C2 was upregulated in P. merus as a whole, whereas the expression of TNF‐α did not change significantly in any of the tissues, which might be a kind of immune response of P. merus against K. pneumoniae infection. This study provides an important theoretical basis for the in‐depth exploration of the pathogenic mechanism of K. pneumoniae in fish and the immune response that occurs after the disease is contracted in fish, as well as theoretical support for the development of effective preventive and therapeutic strategies against K. pneumoniae ‐infected aquatic animals in the future.